A hybrid metaheuristic algorithm for the capacitated location routing problem (2015)
This paper addresses the Capacitated Location-Routing Problem (CLRP) in which the aim is to determine the depots to be opened, the customers to be assigned to each open depot, and the routes to be performed to fulfill the demand of the customers. The objective is to minimize the sum of the cost of the open depots, of the used vehicle costs, and of the variable costs associated with the distance traveled by the performed routes. In this paper, a Granular Tabu Search (GTS) with different diversification strategies within a Iterated Local Search (ILS) is proposed to solve the CLRP. A shaking procedure is applied whenever the best solution found so far is not improved for a given number of iterations. Computational experiments on benchmark instances taken from the literature show that the proposed approach is able to obtain, within short computing times, high quality solutions illustrating its effectiveness.